Dekafeinasi Menggunakan Metode Ultraviolet-Visible Spectroscopy dan PLS-DA - Meinilwita Yulia; Aniessa Rinny Asnaning; Diding Suhandy (Politeknik Negeri Lampung., 2018)
This present research is an application of UV-VIS spectroscopy and SIMCA method toÂ distinguish robusta ground roasted coffee from Sumatera and Java. Spectral dataÂ measurement of the filtered and diluted aqueous coffee samples was performed using a UV-VIS spectrometer (Genesys â„¢ 10S UV-Vis, Thermo Scientific, USA). SIMCA model was constructed for each class, SIMCA model of Sumatera robusta coffee and SIMCA model of Java robusta coffee. Prediction results show that all predictive samples are successfully grouped correctly according to their classes using the developed SIMCA model, except for S14aPA sample that fail to be classified as robusta coffee of Sumatra. Based on the results of the discriminant power plot analysis, it is concluded that in general the contribution of wavelengths between 200-350 nm is higher than that of the wavelength between 350-600 nm. Several wavelengths with very high contribution (high discriminant power value) and seen as peaks on the plot are 245 nm, 253 nm, 264 nm, 316 nm and 327 nm.